Outcome and Clinical Management of 275 Patients With Advanced Ovarian Cancer International Federation of Obstetrics and Gynecology II to IV Inside the European Ovarian Cancer Translational Research Consortium—OVCAD. Issue 2 (1st February 2013) - Chekerov, Radoslav; Braicu, Ioana; Castillo-Tong, Dan Cacsire; Richter, Rolf; Cadron, Isabelle; Mahner, Sven; Woelber, Linn; Marth, Christian; Van Gorp, Toon; Speiser, Paul; Zeillinger, Robert; Vergote, Ignace; et al.
Abstract : Introduction: The Sixth Framework Program European Union project OVCAD, "Ovarian Cancer—Diagnosis of a Silent Killer, " aimed to investigate new predictors for early detection of minimal residual disease in epithelial ovarian cancer (EOC). Here we present the main pathologic, surgical, and chemotherapy characteristics of the OVCAD patient cohort. Methods: Between February 2005 and December 2008, 5 European gynecologic cancer centers (WP2 group) enrolled prospective 275 consecutive patients with EOC into this translational study. Inclusion criteria were as follows: advanced International Federation of Obstetrics and Gynecology II to IV stage, cytoreductive surgery, platinum-based chemotherapy, and collected tumor samples. WP2 coordinated the implementation, screening, and recruiting of the patients and tumor samples into a Web-based data bank according established standard operating procedures. Results: Median age at the time of diagnosis was 58 years. Most patients presented advanced high-grade EOC: International Federation of Obstetrics and Gynecology III/IV (94.5%), grade 2/3 (96%), serous histology (86.2%), ascites (76%), peritoneal carcinomatosis (67.6%), and lymph node involvement (52%). The most common surgical procedures were omentectomy (92.4%), bilateral salpingo-oophorectomy (90.9%), hysterectomy (77.3%), pelvic (69.5%) and paraaortic (66.9%) lymphadenectomy, and large (37.7%) or small bowel resection (13.4%). Patients were treated commonly with platinum-based therapy (98.2%). The macroscopic cytoreduction rate was 68.4%. After a median follow-up of 37 months, 70 patients (25.5%) developed a platinum-resistant recurrence. Biological materials such as tumor and paraffin tissue, ascites, and blood samples were collected consecutively. Conclusions: The implementation of the OVCAD cohort demonstrated the feasibility and advantages of an open, prospective, and multicenter recruitment inside a translational research study. Essential was the predefinition of all inclusion criteria, standard operating procedures, and Web-based software, which enabled the prospective patient recruitment and tissue sampling, minimizing institutional bias and variability in the quality of the biological samples. The translational concept of the OVCAD study does not conflict with the state-of-the-art surgical and chemotherapy management and guaranteed an improved outcome of patients with EOC.